1979
DOI: 10.1126/science.224454
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Ganglion Infection by Thymidine Kinase-Negative Mutants of Herpes Simplex Virus

Abstract: The incidence of trigeminal ganglion infection after corneal inoculation of guinea pigs with thymidine kinase-negative mutants of herpes simplex virus was markedly reduced compared to infection after inoculation of thymidine kinase-positive virus. Thymidine kinase-negative herpes simplex virus replicated well in ocular tissues in which dividing or potentially dividing cells were present, but not in trigeminal ganglion infection of nondividing neurons. Thymidine kinase-positive virus, however, replicated well i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(113 citation statements)
references
References 8 publications
9
102
2
Order By: Relevance
“…That is to say that peripheral replication of HSV may induce a non-permissive environment for viral replication in neurons innervating the site of replication. Animal models using corneal infections, have demonstrated that infectious HSV is not detected within trigeminal ganglia until 48 ± 72 h post-infection (Coen et al, 1989;Jenkins and Martin, 1990;Tenser and Edris, 1987). This delay would allow for the establishment of a IL-1/NGF/Oct-2-mediated non-permissive environment.…”
Section: A Viral Vector For Gene Therapymentioning
confidence: 99%
“…That is to say that peripheral replication of HSV may induce a non-permissive environment for viral replication in neurons innervating the site of replication. Animal models using corneal infections, have demonstrated that infectious HSV is not detected within trigeminal ganglia until 48 ± 72 h post-infection (Coen et al, 1989;Jenkins and Martin, 1990;Tenser and Edris, 1987). This delay would allow for the establishment of a IL-1/NGF/Oct-2-mediated non-permissive environment.…”
Section: A Viral Vector For Gene Therapymentioning
confidence: 99%
“…More recent studies using genetically engineered TK-deletion mutants have shown that an HSV-2 mutant cannot establish either acute or latent ganglionic infection in mice (McDermott et al, 1984;Tenser & Edris, 1987). Similarly, an HSV-1 mutant was shown to be latency-negative in mice but to establish latent infection in at least a proportion of infected rabbits, suggesting that the host may also be a determinant in the establishment of latent infection (Meignier et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Since the dPK is not essential for virus replication in tissue culture, this conservation suggests that the VZV dPK gene may be important in aspects of infection in vivo. Studies of animal models of HSV infection suggest that the HSV TK may be involved in neurovirulence and also may be important in the establishment of latency (Field, 1982;Price & Khan, 1981;Tenser & Dunstan, 1979;Tenser & Edris, 1987;Tenser et al, , 1981. The high level of VZV dPK conservation also facilitated the recognition of mutations that were likely to be responsible for the loss of dPK activity in the acyclovir-resistant strains studied, since there were single changes between wt parents and drugresistant mutants derived from them.…”
mentioning
confidence: 99%